1980
DOI: 10.1002/dev.420130506
|View full text |Cite
|
Sign up to set email alerts
|

Learned persistence at 11–12 days but not at 10–11 days in infant rats

Abstract: In 2 experiments using milk-suckling from an anesthetized dam as the reinforcer, evidence is presented that the transitional age in rat pups for learning of persistence as a result of appetitive partial reinforcement is between 11 and 12 days of age. In Experiment I, pups 12-13 days of age showed the partial reinforcement extinction effect (PREE) whereas 10-11-day olds did not. In Experiment II, pups trained at 11-12 days and tested at Day 13 did show a PREE at Day 13 but those trained at 10-11 days did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 20 publications
(6 reference statements)
2
23
0
Order By: Relevance
“…In infant rats it has been reported that learned behavioral persistence defined through heightened responsiveness during extinction emerges after postnatal Day 12. Younger pups trained under a continuous reinforcement schedule appear not to exhibit dramatic increases during extinction in terms of instrumental behaviors (locomotion in a runway) leading towards suckling and milk reinforcement (Chen & Amsel, 1980). According to the present study, learned perseverance is likely to be observed in 5-and 6-day-old pups under an experimental framework involving the contingency of suckling-related behaviors and milk reinforcement.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In infant rats it has been reported that learned behavioral persistence defined through heightened responsiveness during extinction emerges after postnatal Day 12. Younger pups trained under a continuous reinforcement schedule appear not to exhibit dramatic increases during extinction in terms of instrumental behaviors (locomotion in a runway) leading towards suckling and milk reinforcement (Chen & Amsel, 1980). According to the present study, learned perseverance is likely to be observed in 5-and 6-day-old pups under an experimental framework involving the contingency of suckling-related behaviors and milk reinforcement.…”
Section: Discussionmentioning
confidence: 90%
“…It can represent an alternative tool for the ontogenetic analysis of basic learning and memory processes as well as for the examination of the structure and dynamics of suckling behavior. Relatively brief and non-invasive techniques involving operant conditioning in infant rats are scarce (But see, Alberts & May, 1984;Chen & Amsel, 1980;Johanson & Hall, 1979;Lithgow & Barr, 1984). Analogous techniques developed for human babies have allowed valuable contributions for understanding the acquisition, retention and expression of early memories derived from the contingency of age-specific behaviors and availability of positive reinforcement (e.g., Rovee-Collier, 1987;Rovee-Collier & Barr, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Their rapid extinction is ensured by the fact that they do not exhibit the partial reinforcement extinction effect before 11 to 13 days of life (Chen and Amsel, 1980). Corresponding studies with human infants are lacking, as are studies of extinction with infants more generally.…”
Section: Pruning Excessive Associationsmentioning
confidence: 99%
“…Adults typically receive partial reinforcement to slow the extinction of conditioned fear (e.g., LaBar, Gatenby, et al, 1998), but very young infants do not exhibit a partial reinforcement effect during extinction (Chen and Amsel, 1980). Adults are usually tested for spontaneous recovery within a few days of extinction, whereas infants are often tested over their entire forgetting function.…”
Section: Pruning Excessive Associationsmentioning
confidence: 99%
“…Beyond this general trend, however, we have found that the PREE appears much earlier in ontogeny than do other paradoxical effects. The PREE first appears at 12-14 days (Chen & Amsel, 1980;Letz, Burdette, Gregg, Kittrell, & Amsel, 1978), whereas the MREE fails to appears clearly until about 21 days (Burdette, Brake, Chen, & Amsel, 1976;Chen, Gross, & Amsel, 1981;; SNC first appears at 25-26 days (Chen et al, 1981;; and there is no evidence of the OEEprior to 25-26 days . The sequence of appearance of these extinction effects remains to be explained by theories that attribute these effects to a common set of learning mechanisms.…”
mentioning
confidence: 97%